(untitled) (Innovations in Environmental Economics, 2025)
In recent decades, an excessive focus on financial indicators and short-term economic growth, without sufficient attention to social and environmental consequences, has created significant challenges for economic sustainability and social welfare. This situation highlights the necessity of reconsidering the role of accounting information systems and moving toward more innovative accounting approaches. Social and environmental accounting, as an emerging branch of accounting, seeks to identify, measure, and report the social and environmental impacts of economic activities and can play a significant role in strengthening sustainable economic governance. The present study aims to examine and clarify the role of social and environmental accounting as a tool for sustainable economic governance through a systematic review of the scientific literature. In terms of methodology, this research is descriptive–analytical and was conducted using a systematic literature review approach. Relevant studies published in reputable national and international scientific databases were screened and selected, and their contents were analyzed using qualitative content analysis. The findings indicate that social and environmental accounting, by enhancing transparency and accountability and reducing information asymmetry, provides a basis for improving policymaking and managerial decision-making processes and can contribute to directing investments toward sustainable activities. Nevertheless, challenges such as the absence of unified standards, difficulties in measuring non-financial impacts, implementation costs, and the risk of symbolic reporting limit the effectiveness of this approach. The findings of this study emphasize the necessity of developing institutional frameworks and standardizing social and environmental accounting in order to ensure their effective application in sustainable economic governance.